A review of interferometry for geometric measurement. (4th September 2018) - Yang, Shuming; Zhang, Guofeng
Abstract: As high-precision measuring instruments have developed, interferometers have been widely applied in the measurement of lengths and of the shape of surfaces, with nanometer precision. The emergence of the laser is one of the revolutions that has led to a well-defined traceability route to the definition of the meter via interferometry. Another change is the ever-increasing adoption of detector arrays substituting for conventional methods of recording and analyzing interferograms. New applications have also arisen from the adoption of microscopes, optical fibers, chip-level components and diffractive optical elements, developing enhanced analogues of conventional interferometers, which have the advantages of high integration, low noise levels, and complete sets of measuring instruments with a high level of automation. Since the requirements for measurement parameters and the environment are becoming more complex, we expect that the related instruments will play a progressively significant role in the progress of advanced manufacturing processes and quality control. Multi-sensor integrated flexible measurement methods have been proposed to perform measurements with holistic, more accurate and reliable information. However, most of the proposed methods are not intelligent and are highly integrated, providing only specific solutions for given measuring tasks. In this paper, the principles, progress, prospects and development trends of interferometry are reviewed.